Sciaphila atra (Triuridaceae), a new mycoheterotrophic species from Borneo - Dančák, Martin; Hroneš, Michal; Sochor, Michal (Phytotaxa, 2020)
Sciaphila atra (Triuridaceae) from northern Borneo is described and illustrated. This species is similar to Sciaphila thaidanica from northern Thailand, but differs in distinctly darker stem and flowers, lower number of flowers, larger female flowers which usually have more tepals and wider tepals of male flowers. Taxonomy of Sciaphila secundiflora species complex is discussed in the paper. Key to currently accepted species of Sciaphila in Borneo is included.